Surgical stabilization of the ipsilateral scapula and rib fractures using the mirror Judet approach: a preliminary result - Chang-Han Chuang; Chin-Kai Huang; Chia-Ying Li; Ming-Hsien Hu; Pei-Yuan Lee; Po-Ting Wu (BMC Musculoskeletal Disorders, 2022)
Abstract Background We report our preliminary results using a single approach, the mirror Judet approach, for patients with both ipsilateral scapula and multiple rib fractures. Methods Five consecutive patients [median age: 56 years (range: 44 ~ 60)] with ipsilateral scapula and multiple rib fractures that met the surgical indications were retrospectively reviewed. A single approach, the mirror Judet approach, was used for surgical stabilization of the scapula and targeted rib fractures. Thoracoscopic surgery was performed first for management of associated lung lesions and marking the targeted rib. All patients received the same rehabilitation protocol and a minimum 12-month follow-up. Results All surgically-fixed fractures eventually united without malunion. No complaints of intercostal neuralgia, infection, or other complications were seen. The mean range of motion in the injured shoulder returned to at least 90% of the contralateral side range. The mean Disabilities of the Arm, Shoulder, and Hand score at the 12th month was 2.0 (range: 0-7). All patients were able to return to their previous work. Conclusion The mirror Judet approach allows for the surgical stabilization of the ipsilateral scapula and multiple rib fractures using the same approach and provides acceptable functional outcomes in well-selected patients. Level of evidence Level IV.